1984
DOI: 10.1007/bf00327930
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary relationship between Tn21-like elements and pBP201, a plasmid from Klebsiella pneumoniae mediating resistance to gentamicin and eight other drugs

Abstract: We have characterized pBP201 one of the plasmids from a collection of 46 strains producing adenylyltransferase ANT(2") (Schmidt 1984). It confers resistance to sulphonamides and produces aminoglycoside adenylyltransferases AAD(3") and ANT(2") and beta-lactamase TEM-1. Plasmid pBP201 has a size of 24.8 kilobases (kb) and contains TnA and a Tn21-related element, Tn4000 delta, with deletions in mer and the termini and a substitution at tnpR. In complementation assays with transposition-deficient mutants of Tn21 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
51
0
1

Year Published

1988
1988
1992
1992

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 53 publications
2
51
0
1
Order By: Relevance
“…Also, the 59-base element supplied by the first cassette may favor subsequent integrations on either side of the aadA cassette, as shown for the aadA stems in Fig. 3 (42,55,60 (Fig. 4) …”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Also, the 59-base element supplied by the first cassette may favor subsequent integrations on either side of the aadA cassette, as shown for the aadA stems in Fig. 3 (42,55,60 (Fig. 4) …”
mentioning
confidence: 98%
“…The evolution of some of these elements, specifically the Tn21-like transposons and related plasmids, by site-specific integration of antibiotic resistance genes has been described in recent years (3,11,32,42,60,61). These elements have been shown to possess a common structure, the integron (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1-Lactamase genes are part of transposons, and it remains to be established how they became associated with these elements (19,31). Single-resistance determinants have been shown to be part of transposons, such as in Tn3.…”
mentioning
confidence: 99%
“…The characterization of multiresistance elements, plasmids and transposons, related to bacterial transposon Tn2J revealed that rearrangements involving antibiotic resistance genes were occurring in the vicinity of the streptomycin-spectinomycin (aadA) and sulfonamide (sull) resistance regions (20,40,50,56,62,63). Stokes and Hall (55) have defined the elements borne on these multiresistance plasmids and transposons as integrons, a novel family of potentially mobile DNA elements which are composed of two conserved segments between which discrete units, ordinarily antibiotic resistance genes, have been integrated as gene cassettes.…”
mentioning
confidence: 99%